MDC-Checker: A novel network risk assessment framework for multiple domain configurations. Issue 86 (September 2019) - Bai, Wei; Pan, Zhisong; Guo, Shize; Chen, Zhe; Xia, Shiming
Abstract: It is a challenging task to generate correct network configurations to minimize the attack surface while meeting practical requirements, especially when the interdependent relationships between configurations scattered across physical, network and information domain are taken into consideration. As configurations in different domains are commonly generated separately while their complex inter-relationships are ignored, extra vulnerabilities would be introduced. This paper proposes a novel risk assessment framework named MDC-Checker to help network administrators to assess the risk involved. Firstly, the framework extracts the semantics from multiple domain configurations and network documents. Then, the Multiple Domain Semantics Graph (MDSG) and the Privilege Dependency Graph (PDG) are established in sequence to reason user actual privileges from their initial privileges. Finally, the differences between user deserved privileges and user actual privileges are used to measure the impact of multiple domain configurations on network security. A simulated network scenario with different sets of configurations is employed to validate the effectiveness and scalability of our framework and approach. The experimental results show that the framework captures the influences of multiple domain configurations on network security successfully and the approach is scalable to different sizes of the network.